臺灣中小學奈米科技實驗教材之內容分析 Content Analysis of Nanotechnology Experimental Teaching Materials in Primary and Secondary Schools in Taiwan - 趙毓圻 Yu-Chi Chao; 熊召弟 Chao-Ti Hsiung; 于曉平 Hsiao-Ping Yu (National Taiwan Normal University, 2011)
本研究旨在探究奈米國家型第一期人才培育計畫（2003至2008年）中小學種子教師自主發展的實驗教材所含有的奈米科技重要概念的出現頻率和關聯性。樣本包含209 份教材，以Stevens、Sutherland 與Krajcik（2009）提出的九項奈米尺度科學與工程重要概念：尺寸與尺度、物質構造、尺寸效應、力與交互作用、量子效應、自組裝、工具與儀器、模型與模擬、科學、科技與社會等為分析類目，首先依照各重要概念的定義，編製「奈米科技關鍵詞彙表」，並使用Excel 計數功能，分析國小、國中和高中各學習年段教材中的重要概念出現頻率和關聯性。研究結果發現：各年段中，高中實驗教材含有的奈米科技關鍵詞彙數量最多，且各重要概念間呈現高關聯性；整體中小學實驗教材的各重要概念出現頻率和相互關聯性的結構裡，以「尺寸與尺度」、「物質構造」和「尺寸效應」呈高出現頻率及高關聯性。本研究結果可作為未來建構臺灣中小學奈米科技課程指標，以及發展奈米科技教材之參考。 This study investigates the occurrence and relationships among significant nanotechnology concepts employed in the experimental teaching materials developed by primary and secondary seed teachers during Phase I of the National Science and Technology Program in Nanotechnology (2003 to 2008). This study adopts the core principles or "big ideas" of nanoscale science and engineering education, namely size and scale, structure of matter, forces and interactions, quantum effects, size-dependent properties, self-assembly, tools and instruments, models and simulations, and science, technology, and society (Stevens, Sutherland, & Krajcik, 2009), to compile a checklist of scientific terms in nine dimensions, and uses Microsoft Excel to analyze 209 teaching materials from each educational level. The investigation results revealed that 10 to 12 teaching materials from each level used more scientific keywords and had stronger relationships; the highest occurrence frequency and strongest relationships were between size and scale, structure of matter, and size effects. The results of this study can provide a reference for establishing nanotechnology curriculum indicators of primary and secondary education and developing nanotechnology teaching materials.